2020
DOI: 10.1080/13102818.2020.1775118
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as a potential COVID-19 treatment from the pharmacokinetic point of view: antiviral levels are not likely attainable with known dosing regimens

Abstract: The broad-spectrum antiparasitic agent ivermectin has been very recently found to inhibit SARS-CoV-2 in vitro and proposed as a candidate for drug repurposing in COVID-19. In the present report the in vitro antiviral activity end-points are analyzed from the pharmacokinetic perspective. The available pharmacokinetic data from clinically relevant and excessive dosing studies indicate that the SARS-CoV-2 inhibitory concentrations are not likely to be attainable in humans.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 24 publications
5
86
0
1
Order By: Relevance
“…Like previous reports, our in-vitro studies found that ivermectin has nonselective toxicity to the ATCC E6 Vero cells at ≤50 μM and 16.67 μM based on the number of nuclei counted. This shows that high doses (>16.67 μM) of ivermectin have high cytotoxicity as reported by other groups 129,130 , and this must be considered when preparing to use this drug in COVID-19 clinical trials as its currently approved dosage is very low (25mg) 131 . Target Proteins (Receptors) preparation.…”
Section: Resultssupporting
confidence: 63%
“…Like previous reports, our in-vitro studies found that ivermectin has nonselective toxicity to the ATCC E6 Vero cells at ≤50 μM and 16.67 μM based on the number of nuclei counted. This shows that high doses (>16.67 μM) of ivermectin have high cytotoxicity as reported by other groups 129,130 , and this must be considered when preparing to use this drug in COVID-19 clinical trials as its currently approved dosage is very low (25mg) 131 . Target Proteins (Receptors) preparation.…”
Section: Resultssupporting
confidence: 63%
“…Like previous reports, our in-vitro studies found that ivermectin has nonselective toxicity to the ATCC E6 Vero cells at ≤50 μM and 16.67 μM based on the number of nuclei counted. This shows that high doses (>16.67 μM) of ivermectin have high cytotoxicity as reported by other groups 131,132 , and this must be considered when preparing to use this drug in COVID-19 clinical trials as its currently approved dosage is very low (25mg) 133 Target Proteins (Receptors) preparation. Protein preparation was performed using the Protein Preparation Wizard in Maestro 1 .…”
Section: Resultssupporting
confidence: 62%
“…recently suggested that in vitro inhibitory concentrations of 5umol/L (those needed for a total eradication of SARS-CoV-2 in in vitro studies) would not be attainable even using high doses of ivermectin (2000ug/kg) [4,14]. The study has some limitations.…”
Section: Plos Onementioning
confidence: 92%